The life of Mark Twain : the early years, 1835-1871 - Scharnhorst, Gary (Mark Twain and his circle series., 2018)
This book begins the first multi-volume biography of Samuel Clemens to appear in over a century. In the succeeding years, Clemens biographers have either tailored their narratives to fit the parameters of a single volume or focused on a particular period or aspect of Clemens's life, because the whole of that epic life cannot be compressed into a single volume. In The Life of Mark Twain, Gary Scharnhorst has chosen to write a complete biography plotted from beginning to end, from a single point of view, on an expansive canvas. With dozens of Mark Twain biographies available, what is left unsaid? On average, a hundred Clemens letters and a couple of Clemens interviews surface every year. Scharnhorst has located documents relevant to Clemens's life in Missouri, along the Mississippi River, and in the West, including some which have been presumed lost. Over three volumes, Scharnhorst elucidates the life of arguably the greatest American writer and reveals the alchemy of his gifted imagination.